Medische ontwikkelingssamenwerking in Centraal-Afrika - A. De Schaepdryver (Afrika Focus, 1990)
The author describes the Project of Medical Cooperation between the Medical Faculties of the University of Ghent and the National University of Rwanda in Butare.The objectives of this project, which started in 1966, were the following: (l)to organize and dispense the theoretical education andpractical training at the G.P.-level; (2) to structure the postgraduate education of alumni selected for higher education posts; (3) to take care of the postgraduate training of specialists; (4) to organize the continuing education of health personnel; (5) to promote and participate in medical research. The results of the Project were, in 1984: (1) at the level of health personnel: the education and training of 220 physicians, 19 university lecturers and 15 specialists; (2) at the level of the infrastructure: the building of the Medical Faculty facilities, the pediatric and medical policlinics and clinics, the community health service for adults; the adaptation of the gynecological-obstetrical policlinic and clinic and of the community health service for children; the founding of the Faculty library, secretariat and workshop, (3) at the research level: the founding and development of the University Center for Research on Traditional Pharmacopoeia and Medicine, aimingat: a) the valorization and integration of traditional medicine; b) the study of Rwandese medicinal plants; c) the local production of pharmaceutical preparations of plant origin andorganic raw materials. The attention is drawn to the importance of the postgraduate education in Belgium, for periods of 5 years, of 25 Rwandese medical alumni, which resulted in 15 Ph.D. -theses and a nearly complete rwandization of the Faculty of Medicine and University Hospital in Butare. A pairing Agreement Butare-Ghent has taken the relief of the Project,insuring its continuity through visiting lecturers, and the coaching of trainees and of research projects in various fields of the local pathology.